Comparison of Efficacy of Acupuncture-Related Therapy in the Treatment of Rheumatoid Arthritis: A Network Meta-Analysis of Randomized Controlled Trials - Wan, Renhong; Fan, Yihua; Zhao, Anlan; Xing, Yuru; Huang, Xiangyuan; Zhou, Liang; Wang, Ying (Frontiers in Immunology, 2022)
Background: The refractory, repetitive, and disabling characteristic of rheumatoid arthritis (RA) has seriously influenced the patients’ quality of life, and makes it a major public health problem. As a classic complementary and alternative therapy, acupuncture is usually applied for RA combined with disease modifying anti-rheumatic drugs (DMARDs). However, there are various types of acupuncture, and the curative effects are different in different acupuncture therapies. In this study, we evaluated the clinical efficacy of different acupuncture therapies combined with DMARDs in the treatment of RA. Methods: The randomized controlled trials (RCTs) of acupuncture combined with DMARDs in the treatment of RA were searched in both English and Chinese database of PubMed, Cochrane Library, EMBASE, Web of Science, CNKI, VIP database, Wanfang, and SinoMED, up to October 2021. Literature screening, data extraction, and evaluation of the risk of bias were carried out independently by two researchers, and the data were analyzed by Stata14.2 and GeMTC 0.14.3 software. Results: A total of 32 RCTs were included, including 2115 RA patients. The results of network meta-analysis were as follows: in terms of improving DAS28 score, Electro-acupuncture + DMARDs has the best efficacy. In terms of improving VAS score, Fire Needle + DMARDs showed the best efficacy. In terms of improving morning stiffness time, acupuncture related therapies combined with DMARDs were not better than DMARDs alone in improving morning stiffness time in RA patients. In terms of reducing CRP and ESR, Fire Needle + DMARDs showed the best efficacy. In terms of reducing RF, Moxibustion + DMARDs has the best efficacy. Conclusions: The comprehensive comparison of the outcome indicators in 8 different treatments indicates that electro-acupuncture combined with DMARDs is the best combined therapy in improving DAS28 score, while in terms of improving pain and serological markers, fire needle combined with DMARDs and moxibustion combined with DMARDs were the best combined therapies. However, it is impossible to find out which is better between fire needle and moxibustion due to the limited studies. Clinically, appropriate treatment should be selected according to the actual situation.